1978
DOI: 10.1017/s0022172400024773
|View full text |Cite
|
Sign up to set email alerts
|

Commercial factor VIII associated hepatitis, 1974–75, in the United Kingdom: a retrospective survey

Abstract: SUMMARYA retrospective survey of transfusion hepatitis associated with a brand of commercial Factor VIII was carried out in 24 Haemophilia Centres from January 1974 until December 1975. Of 371 patients who were transfused with this product, and were followed up, 78 cases of hepatitis affecting 66 patients were found (17-7 %). Two types of hepatitis were observed: hepatitis B and non-B hepatitis, the latter with an incubation period of between 8 and 60 days. Twelve patients contracted two types of hepatitis, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Because of pool size and because manu facturing processes until recently have not included a heat ing step in the preparation of concentrate, the final product has often been contaminated with viruses: recipients of factor concentrates have been exposed to Epstein-Barr and cytomegalovirus [9], hepatitis B and hepatitis non-A non-B viruses [10] and to the human immunodeficiency virus (HIV) [11]. The risk to recipients from factor concentrates containing these and other viruses is of great concern, par…”
Section: Introductionmentioning
confidence: 99%
“…Because of pool size and because manu facturing processes until recently have not included a heat ing step in the preparation of concentrate, the final product has often been contaminated with viruses: recipients of factor concentrates have been exposed to Epstein-Barr and cytomegalovirus [9], hepatitis B and hepatitis non-A non-B viruses [10] and to the human immunodeficiency virus (HIV) [11]. The risk to recipients from factor concentrates containing these and other viruses is of great concern, par…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that patients with haemophilia who receive infusions of clotting factor concentrates prepared from large plasma pools are exposed to the well known risk of viral infections, such as hepatitis B virus [Craske et al, 1978;Morfini et al, 19861, non-A, non-B hepatitis viruses [Kernoff et al, 19841, and the human immunodeficiency virus [Ludlam et al, 19851. One report [Mortimer et al, 19831 has shown that human parvovirus, now designated B19 [Siegl et al, 19851, is transmitted by blood products, as indicated by evidence of viraemia, following the infusion of a commercial Factor VIII concentrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, today non-A, non-B hepatitis is the major type of posttransfusion hepatitis [1,3]. A similar trend has been noted for hepatitis following coagulation factor therapy [2], The present retrospective study includes hepatitis cases occurring in a Hemophiliac…”
mentioning
confidence: 66%
“…However, most cases of posttrans-most evident in the high hepatitis attack rate at first time treatment with brand II com pared to brand I. Attack rates for different batches of the two brands, as demonstrated by Craske et al [2], could not be given since the batch numbers of brand II were not known. However, it seems likely that differ ent infectious batches were used, since about 10-15 different batches of this brand are imported by Sweden annually.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation